Mitochondrial epigenetics brings new perspectives on doubly uniparental inheritance in bivalves - Émélie Leroux; Hajar Hosseini Khorami; Annie Angers; Bernard Angers; Sophie Breton (Scientific Reports)
Abstract Mitochondrial epigenetics, particularly mtDNA methylation, is a flourishing field of research. MtDNA methylation appears to play multiple roles, including regulating mitochondrial transcription, cell metabolism and mitochondrial inheritance. In animals, bivalves with doubly uniparental inheritance (DUI) of mitochondria are the exception to the rule of maternal mitochondrial inheritance since DUI also involve a paternal mtDNA transmitted from the father to sons. The mechanisms underlying DUI are still unknown, but mtDNA methylation could play a role in its regulation. Here, we investigated mtDNA methylation levels and machinery in gonads of the mussel Mytilus edulis using methods based on antibodies, enzymatic cleavage and methylome sequencing. Our results confirm the presence in mitochondria of methylated cytosines and adenines and methyltransferases and unveil a more variable cytosine methylation state among males than females. Also, spermatid mtDNA is always methylated, while only few spermatozoa present methylated mtDNA suggesting a relation between cytosine methylation and development stage of male gametes. We propose that mtDNA methylation could play a role in the different fates of the parental mtDNAs in male and female embryos in M. edulis. Our study provides novel insights into the epigenetic landscape of bivalve mtDNA and highlights the multiple roles of mtDNA methylation in animals.